Pemikiran Wahbah al-Zuhaili tentang Hukum Riba dalam Transaksi Keuangan pada Kitab Fiqih Islam Wa Adillatuhu - Nyanyang Nyanyang (Prodi Hukum Ekonomi Syariah (Muamalah), 2020)
This research explains the problem of usury law and its interpretation in financial transactions personally conducted by the public in insurance institutions as well as bank interest from the thought wahbah zuhaili and provide the solution. According to him, usury is divided into the first three types, riba fadh, second, riba yad and third riba nasiah. Wahbah zuhaili argues that the forbidden interest is usury that multiplies both the little and the amount of interest obtained because it is the same as the rib element. The prohibition of usury (usurios) in Islam based on moral and humanitarian considerations because the essence of usury prohibition is the elimination of all forms of economic practice that cause injustice and injustice. And the impact of interest on the economy will lead to a slowdown in economic growth. This method of writing a journal is based on the study of the library by conducting an in-depth review of wahbah zuhaili's books, books, interpretations and writings on bank interest, usury and related to it. The purpose of this writing is to know the laws, practices of usury and solutions in order to avoid the practice of usury inflicted on the economy.